Dorsal inlay inner preputial graft for primary hypospadias repair - Rajendra B. Nerli; Ajaykumar K. Guntaka; Ranjeet A. Patil; Pravin B. Patne (Wolters Kluwer Medknow Publications, 2014)
Background: The most commonly performed operation to repair distal hypospadias is the Tubularised incised plate (TIP) repair. The key step is midline incision of the urethral plate, which widens a narrow plate and converts a flat into a deep plate groove, ensuring a vertical, slit neomeatus and a normal-calibre neourethra. At times in cases of proximal hypospadias, the urethral plate is very narrow and needs to be augmented or substituted for further tubularisation. We report our experience with primary single stage dorsal inlay urethroplasty using preputial skin grafts. Patients and Methods: Children with proximal hypospadias with a narrow urethral plate formed the study group. Children needing transection of the urethral plate, having undergone circumcision/hypospadias repair previously or having an inadequate prepuce was excluded. Results: Twelve children with a mean age of 48.83 months underwent primary dorsal inlay preputial graft urethroplasty for proximal hypospadias with a very narrow urethral plate. At an average follow-up of 42.16 months, 2 (16.66%) children had a breakdown of ventral shaft skin. None of the children had meatal stenosis, and none of these 12 children developed urethrocutaneous fistula. Conclusion: Primary dorsal inlay inner preputial graft urethroplasty successfully fulfills all traditional hypospadias repair criteria. It offers a viable, safe, rapid and easy option in the management of proximal hypospadias with a narrow urethral plate.